PENGARUH EARNING MANAJEMEN MEMEDIASI HUBUNGAN ANTARA GOOD CORPORATE GOVERNANCE DAN KINERJA PERUSAHAAN - Bahrul Ilmi Arief Sayyidi; R.A Norromadani Yuniati; Danis Maulana (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2022)
Growth of Indonesia's maritime industry has grown rapidly, seen from increase number of domestic ships and loading unloading of goods. Development company will certainly followed by the amount demands from company's stakeholders, so optimization performance is expected to increase value oriented for all parties. Data shows in last 2 years, stock prices of most industries have decreased. This indicates company's performance decreases when demands of the company's stakeholders are high. One way to improve company performance is by implementing good corporate governance (GCG). This study aims to analyze effect of GCG implementation on company performance in sea transportation sub-sector listed on IDX during 2018 - 2020. Research data sources were obtained from IDX and websites of 15 sample companies using purposive sampling method. Statistical test technique used is SEM-PLS with Outer and Inner model. Results of this study indicate that implementation of GCG has a significant negative effect on company performance, The implementation of GCG has no effect on earning management. Earning management has a positive effect on company performance, and earnings management doesn’t mediate relationship between implementation of GCG on company performance. Because implementation of GCG is not optimal, so company tends to be opportunistic and prioritizes itsreputation.